2018
DOI: 10.1101/319772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic dissection of mitotic spindle positioning in vivo

Abstract: The position of the mitotic spindle determines the plane of cell cleavage, and thereby the location, size, and content of daughter cells. Spindle positioning is driven by dynein-mediated pulling forces exerted on astral microtubules. This process requires an evolutionarily conserved complex of Gα-GDP, GPR-1/2 Pins/LGN , and LIN-5 Mud/NuMA proteins. It remains unknown whether this complex merely forms a membrane anchor for dynein, or whether the individual components have additional functions, for instance thro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 74 publications
4
25
0
Order By: Relevance
“…They also showed that dynein cannot generate enough force to pull the spindle on its own – NuMA must also be recruited ( Figure 1A , bottom). This synergizes with findings from a recent study using worm embryos ( Fielmich et al, 2018 ): targeting the worm equivalent of NuMA with light suffices to move the spindle, while targeting dynein alone does not. This indicates that NuMA may have other roles beyond simply recruiting dynein to the cortex.…”
supporting
confidence: 85%
“…They also showed that dynein cannot generate enough force to pull the spindle on its own – NuMA must also be recruited ( Figure 1A , bottom). This synergizes with findings from a recent study using worm embryos ( Fielmich et al, 2018 ): targeting the worm equivalent of NuMA with light suffices to move the spindle, while targeting dynein alone does not. This indicates that NuMA may have other roles beyond simply recruiting dynein to the cortex.…”
supporting
confidence: 85%
“…These results suggest that cortical dynein targeting is not sufficient for generating cortical pulling forces in human cells, consistent with recent studies demonstrating that human dynein is auto-inhibited ( Torisawa et al, 2014 ; Zhang et al, 2017 ) and dynactin and cargo adaptors are required to activate dynein motility ( McKenney et al, 2014 ; Schlager et al, 2014 ; Zhang et al, 2017 ). Although we cannot exclude the possibility that iLID-Nano mediated cortical targeting of DHC may impair some cortical dynein functions or assemblies in human cells, cortical dynein anchoring with ePDZ-LOVp system in C. elegans is also insufficient to generate cortical pulling forces ( Fielmich et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous optogenetic approaches (Fielmich et al, 2018;Okumura et al, 2018;van Haren et al, 2018;Yang et al, 2013;Zhang et al, 2017), this method allows for global lossof-function of full-length spindle proteins, relying on simple protein tagging rather than domain splitting, with no need of chromophore addition. Moreover, this method may be implemented with other optical perturbations (Milas et al, 2018) and used as "in vivo pulldown" for probing protein-protein interactions in different phases of the cell cycle.…”
Section: An Optogenetic System For Acute Selective and Reversible Rmentioning
confidence: 99%
“…In this work, we developed an optogenetic approach for acute and reversible removal of PRC1 from the spindle to the cell membrane, building upon ideas of dimerization or dissociation induced chemically (Cheeseman et al, 2013;Haruki et al, 2008;Robinson et al, 2010;Wordeman et al, 2016) or by light (Fielmich et al, 2018;Guntas et al, 2015;Okumura et al, 2018;van Haren et al, 2018;Yang et al, 2013;Zhang et al, 2017) to rapidly redistribute proteins. By using our assay on metaphase spindles, we found that bridging fibers promote kinetochore alignment.…”
mentioning
confidence: 99%